A numerical methodology for predicting tool wear in Friction Stir Welding - Hasan, Ahmed; Bennett, Chris; Shipway, P.H.; Cater, S.; Martin, J. (Elsevier, 2017)
A novel methodology for predicting tool wear in FSW based on a CFD model, coupled with a modified Archard equation, is presented considering the effect of the deformation of the highly viscous flow around the tool on tool wear. A validation process is proposed to ensure robust results when using this methodology. A study was carried out to predict the wear on a dome shaped FSW tool, indicating that high wear was predicted at the shoulder edge due to rapidly changing flow, and that the interaction of the axial flow with the pin causes a bifurcation of the flow and an associated increase in pressure at the mid axial position of the pin, again leading to high wear in this location. The proposed approach could be used as a method for calculating tool wear and determining the effective limits of tool use, without the need for experimental trials.